2019
DOI: 10.1155/2019/7823761
|View full text |Cite
|
Sign up to set email alerts
|

Imperatorin Suppresses Anaphylactic Reaction and IgE-Mediated Allergic Responses by Inhibiting Multiple Steps of FceRI Signaling in Mast Cells: IMP Alleviates Allergic Responses in PCA

Abstract: This study is to investigate the effects of imperatorin (IMP) on allergic responses mediated by mast cells, both in vitro and in vivo. Passive cutaneous anaphylaxis (PCA) model was established. Histological detection was performed to assess the ear histology. ELISA and Western blot analysis were used to detect the levels of corresponding cytokines and signalling pathway proteins. IMP decreased the leakage of Evans blue and the ear thickness in the PCA models, in a dose-dependent manner, and alleviated the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
2
17
0
1
Order By: Relevance
“…Hu et al reported that IMP-induced Nrf2 activation effectively upregulated its downstream antioxidants, possibly offering cellular protection to the heart from injury induced by arsenic trioxide (As 2 O 3 ) [76]. Very recently, Xian et al investigated the protective effect of IMP against excess ROS and chronic airway inflammation in OA-administered mice [77]. Treatment with IMP suppressed ROS, proinflammatory cytokines, inflammatory cell infiltration, collagen deposition, and goblet cell hyperplasia.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al reported that IMP-induced Nrf2 activation effectively upregulated its downstream antioxidants, possibly offering cellular protection to the heart from injury induced by arsenic trioxide (As 2 O 3 ) [76]. Very recently, Xian et al investigated the protective effect of IMP against excess ROS and chronic airway inflammation in OA-administered mice [77]. Treatment with IMP suppressed ROS, proinflammatory cytokines, inflammatory cell infiltration, collagen deposition, and goblet cell hyperplasia.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Treatment with IMP suppressed ROS, proinflammatory cytokines, inflammatory cell infiltration, collagen deposition, and goblet cell hyperplasia. These effects have been suggested to be mediated via modulation of Nrf2 signaling following IMP administration [77].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…FcεRI is a high-affinity IgE receptor expressed on the cell surface of mast cells and basophils [9][10][11]. Recently, much attention has been focused on searching for biologically active antiallergic compounds that downregulate FcεRI expression [12,22,23]. Our results showed that EDG and DC induced a decrease in protein, and that the mRNA levels of the cellular FcεRI α-chain may be associated with the suppression of cell-surface FcεRI expression ( Figure 3).…”
Section: Discussionmentioning
confidence: 66%
“…The downregulation of FcεRI expression in effector cells may lead to the attenuation of IgE-mediated allergic reaction. The signaling pathways of MAPK and NF-kB are predominant cascades that are closely related to allergic responses [12]. Chrysanthemum zawadskii var.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium butyrate, an inhibitor of HDACs, can decrease levels of ovalbumin-specific IgE and improve clinical symptoms and nasal mucosa epithelial morphology in a mouse model of allergic rhinitis [86]. PCA reactions can increase expression levels of inflammatory cytokines via the activation of PI3K/AKT, MAPK and NF-κB [87]. HDAC inhibitors such as TSA can inhibit PCA and TpCR [15].…”
Section: Hdacs Inhibitors and Allergic Inflammatory Diseasesmentioning
confidence: 99%